2016
DOI: 10.3109/17435390.2016.1163743
|View full text |Cite
|
Sign up to set email alerts
|

Acute systemic exposure to silver-based nanoparticles induces hepatotoxicity and NLRP3-dependent inflammation

Abstract: Nanoparticles (NPs) are increasingly being commercialized for use in biomedicine. NP toxicity following acute or chronic exposure has been described, but mechanistic insight into this process remains incomplete. Recent evidence from in vitro studies suggested a role for NLRP3 in NP cytotoxicity. In this study, we investigated the effect of systemic administration of composite inorganic NP, consisting of Ag:Cu:B (dose range 1-20 mg/kg), on the early acute (4-24 h post-exposure) and late phase response (96 h pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 54 publications
(64 reference statements)
0
32
0
Order By: Relevance
“…They produce oxidative stress that in turn modulates the autophagic process in the liver, disrupting liver metabolism and homeostasis (65). This hepatic oxidative damage has been reported in both in vitro and in vivo models for AuNPs, SiO 2 NPs, and AgNPs, with differences among the NP compositions (130)(131)(132)(133)(134). However, long-term effects need to be further characterized (65).…”
Section: Nanoparticle Toxicitymentioning
confidence: 99%
“…They produce oxidative stress that in turn modulates the autophagic process in the liver, disrupting liver metabolism and homeostasis (65). This hepatic oxidative damage has been reported in both in vitro and in vivo models for AuNPs, SiO 2 NPs, and AgNPs, with differences among the NP compositions (130)(131)(132)(133)(134). However, long-term effects need to be further characterized (65).…”
Section: Nanoparticle Toxicitymentioning
confidence: 99%
“…The observed changes in the above metabolites underlined that Au@Ag NRs resulted in different metabolic disruptions in mouse liver ( Table 2, 27 metabolite changes: 17 downregulated and 10 upregulated). Similarly, it is reported that Ag NPs can give rise to the decline in mitochondrial membrane potential, the impairment of lysosomal membrane, and even lactate dehydrogenase leakage [4,5,24,25]. Mitochondrial membrane potential is related with electron transport chain in mitochondrion, further reflecting the state of energy metabolism.…”
Section: Organsmentioning
confidence: 87%
“…AgCuB NPs were synthesized and characterized as discussed in [20]. Briefly, 0.1 M salt of silver nitrate, copper sulfate, and boric acid in a ratio of 70:20:10 respectively was mixed in ethylene glycol and after vigorous stirring, 10 mM each of L-cysteine and sodium hydroxide was added in a final volume of 20 ml which was added dropwise to the round bottom flask containing 10 mM of hydrazine hydrate and 10 mM of sodium citrate.…”
Section: Synthesis Of Nanoparticlesmentioning
confidence: 99%
“…The boron has a lower atomic number, as a result, it cannot be detected by EDX spectroscopy; however, B was detected by inductively coupled plasma optical emission spectroscopy (ICP-OES)( Fig. 1H) [20].…”
Section: Nanoparticle Characterizationmentioning
confidence: 99%
See 1 more Smart Citation